Violência entre irmãos: uma realidade desconhecida - Relva, Inês Carvalho; Fernandes, Otília Monteiro; Alarcão, Madalena (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2013)
This article is a review of the literature on sibling violence. Although it is a subject rarely discussed in scientific literature, some research has shown that deserves more attention, given its high prevalence and dangerousness. We have identified some concepts that have been associated with this issue, and presented several studies that point to its high occurrence and risk factors that have been suggested to explain this violence. We, also, do a description of the various definitions of different types of violence (e.g., physical violence, psychological violence and sexual abuse) and analyzed their impact.